Constructing Injectable Bone-Forming Units by Loading a Subtype of Osteoprogenitors on Decellularized Bone Matrix Powders for Bone Regeneration - Xu, Yan; Yan, Shaohang; Chen, Can; Lu, Bangbao; Zhao, Ruibo (Frontiers in Cell and Developmental Biology, 2022)
Bone defect resulted from trauma or tumor is one of the most challenging problems in clinical settings. Current tissue engineering (TE) strategies for managing bone defect were insufficient, owing to without using optimal osteoconductive material and seeding cells capable of superior osteogenic potential, thus their efficacy is instable. Herein, a novel TE strategy was developed for treating bone defect. Firstly, decellularized bone matrix (DBM) was manufactured into powders, and these DBM powders preserve the ultrastructural and compositional properties of native trabecular bone, are non-cytotoxic and low-immunogenic, and are capable of induce the interacted stem cells differentiating into osteogenic linage; Then, a subtype of osteoprogenitor was isolated from mouse long bones, and its high osteogenic potential was identified in-vitro; After that, we constructed a “bone-forming unit” by seeding the special subtype of osteoprogenitors onto the DBM powders. In-vivo performance of the “bone-forming units” was determined by injecting into defect site of a mouse femoral epiphysis bone defect model. The results indicated that the “bone-forming unit” were capable of enhancing bone defect healing by regulating new bone formation and remodeling. Overall, the study establishes a protocol to construct novel “bone-forming unit”, which may be an alternative strategy in future bone TE application.